Variant of Organizational and Functional Adaptation Structures of a Typical Situational Centre to the Emergence of Crisis Situations - Volodymyr Mirnenko; Oleh Hudyma; Vadym Artamoshchenko (Qubahan Academic Journal)
Due to the growing number of crisis situations (CS) in the modern world, such as natural disasters, man-made accidents, pandemics, cyber-attacks, financial crises, wars, and other negative events, it is important for the state to develop and adapt the organizational and functional structures of information and analytical units, including situation centers (SC), to respond effectively to such cases, thereby ensuring the country’s resilience in the face of negative circumstances. The purpose of the study is to consider and analyze a possible option for adapting the organizational and functional structure of a typical SC for more efficient functioning in the context of a CS. The research methods used in the article include content analysis, analysis, induction and hypothetical method. The article highlights the organization of information interaction between state structures during full-scale conflicts, the ways of resolving the SC in such conditions and the measures taken to respond effectively in a timely manner. Particular attention is paid to approaches to information counteraction in crisis management. The authors analyze the experience of countries around the world in establishing and operating SC and developing appropriate organizational and functional structures. Based on the results of the analysis, it is concluded that today there is a tendency to establish and operate crisis centers in countries around the world. However, it has been found that no publication pays sufficient attention to approaches to adaptation (improvement) of the structures of crisis centers to the emergence of the CS. The study is of great importance, since the proposed option of adapting the organizational and functional structure of a typical crisis center to the emergence of a CS opens up new opportunities for understanding effective methods of countering a CS and promotes the development of crisis management strategies, in particular in the context of hybrid confrontation and full-scale war.